Application of CFD to model an aeroengine internal gearbox - Turner, Adam James (2015)
This thesis describes research undertaken to improve computational modelling capability for the internal gearbox (IGB) of an aeroengine. Using the commercial computational fluid dynamics (CFD) software ANSYS FLUENT modelling methodologies for regions within the IGB have been developed, applied and refined.